Experimental Studies on the effects of Chlorpyrifos on Rats I. Histopathological changes - S. H.. El-durssi, Ibrahim; O.S. El-Awami, Ifdial; S. mahmoud, Ghyath; A. Benkhaial, Fahim; Naseb Mohamed, Nura (Al-Mukhtar Journal of Sciences, 2006)
This Study performed to investigate the effect of Chlorpyrifos (one of the most used insecticides)on certain organs in rats. The experimental animals were 110 male rats and were divided into four groups: the first group was used to determine the median lethal dose (LD50) which appeared to be equal to (81.2)mg/Kg B.W. While the second group of rats received an oral daily doses of 1/10 LD50 . The third and fourth groups of rats were administered single oral dose of 1/10 LD50 and 1/30 LD50 respectively. Histopathological findings of the liver revealed a hypertrophy of liver cells with stenosis of the sinusoids, congestion of the blood vessels, necrosis and hemorrhagic spots on the sub capsular spaces. Some hepatic lesions showed fatty changes and liver cirrhosis. While the pulmonary lesions characterized by pulmonary emphysema and hemorrhage with the presence of hyaline casts in their alveoli. The spleen showed congestion, lymphoid depletation and necrosis. The heart showed hypertrophy of its muscle fibers with the presence of petechiation on the subendocardial and subepicardial spaces, with Lymphocytic infiltrations. While sections from the intestine showed hemorrhagic enteritis and slaughing of its epithelial mucosae. Most of the renal and testicular sections which were examined revealed congestion, exudation and necrosis of their tissues with presences of hyaline casts in the renal tubules. Sections from the brain showed congestion, exudation, Lymphocytic infiltration and necrosis of Purkinje’s cells, although encephalitis and meningitis were dominant in most animals.